1993
DOI: 10.1080/09540129308258012
|View full text |Cite
|
Sign up to set email alerts
|

Sexual issues and condom use among injecting drug users

Abstract: Recent surveys of injecting drug users reveal that their injecting behaviours have changed in the light of HIV, but their sexual behaviours have not and, in particular, they remain reluctant to use condoms to reduce the risks of sexual transmission. In an attempt to explore this issue further the present study assessed the behaviours and attitudes of injecting drug users to sexual issues, including condom use. Condom use was low. Obstacles to their use included for some a desire to conceive, for many a belief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 12 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…The studies took place in seven different countries: United States (10), Australia (5), England (3), Canada (2), France (2), Finland (1), and Russia (1). Nine studies collected data from women in substance abuse treatment (including White et al, 1993 whose population also include needle exchange clients), seven from women using drugs or alcohol but not in drug treatment (including a subset of women from Toffol et al, 2011), and eight from other populations where >50% of the group reported drug and alcohol use (i.e., street-based female sex workers, chronically homeless women, incarcerated women, or women living with HIV or hepatitis C). Of note, fourteen studies included details about the specific type of drug(s) used, with more than half (51%) of the women in these studies reporting opioid use and much smaller percentages, alcohol and cocaine.…”
Section: Resultsmentioning
confidence: 99%
“…The studies took place in seven different countries: United States (10), Australia (5), England (3), Canada (2), France (2), Finland (1), and Russia (1). Nine studies collected data from women in substance abuse treatment (including White et al, 1993 whose population also include needle exchange clients), seven from women using drugs or alcohol but not in drug treatment (including a subset of women from Toffol et al, 2011), and eight from other populations where >50% of the group reported drug and alcohol use (i.e., street-based female sex workers, chronically homeless women, incarcerated women, or women living with HIV or hepatitis C). Of note, fourteen studies included details about the specific type of drug(s) used, with more than half (51%) of the women in these studies reporting opioid use and much smaller percentages, alcohol and cocaine.…”
Section: Resultsmentioning
confidence: 99%
“…However, reduction in sexual risk behavior has not been as evident (Baker et al, 1993;White, Phillips, Mulleady, & Cupitt, 1993). Female IDUs in particular are failing to increase condom use as compared with their male counterparts (Calsyn, Saxon, Wells, & Greenberg, 1992).…”
Section: Introductionmentioning
confidence: 90%
“…Studies investigating these relationships among IDUs have found positive attitudes toward condom use, and significant associations between attitudes about condoms and condom use intentions and behaviors, especially for casual partners (Belanger et al, 2002;Corby et al, 1996;Falck et al, 1997;Fernandez et al, 1997;Kasprzyk et al, 1998;Peterson et al, 1992;Schilling et al, 1991). Moreover, qualitative and quantitative research has identified several barriers to condom use among IDUs, including general dislike of condoms, low perceived risk of HIV, and the beliefs that condoms are difficult or inconvenient to use, and are not necessary with monogamous or steady partners (Corby et al, 1996;Weiss et al, 1993;White and Phillips, 1993).…”
Section: Introductionmentioning
confidence: 92%
“…Prior research has found low levels of condom use among IDUs, especially with steady partners and among those who are also using crack cocaine. Further, female IDUs, in particular, are likely to engage in commercial sex work, which places them at increased sexual risk (Anderson et al, 1996;Booth et al, 1993Booth et al, , 2000Corby et al, 1996;Siegal et al, 1996;White and Phillips, 1993). Given these high levels of sexual risk behaviors, there is a clear public health need to identify factors that influence patterns of condom use among male and female IDUs.…”
Section: Introductionmentioning
confidence: 96%